Sea otters are recolonizing southern California in fits and starts. Issue 5 (6th May 2014) - Lafferty, Kevin D.; Tinker, M. Tim
Abstract : After near extinction as a result of the fur trade in the 1700s and 1800s, the southern sea otter slowly reoccupied the core of its range in central California. Range expansion beyond central California is seen as key to full recovery of otters, but the rate of expansion has been sporadic, raising concerns about habitat quality in southern California. To describe the range expansion of sea otters from central into southern California, we used skiff surveys, aerial surveys, and archival time‐depth recorders from 2004 to 2013. These observations show that range expansion began when male otters swam southeast of Point Conception (Cojo Anchorage), perhaps to seek refuge from bad weather and to feed on unexploited resources. After several years of seasonal use by male groups, females began to use the area, leading to reproduction and a secondary increase in abundance. In contrast, a second male group that moved farther down the coast to Coal Oil Point stalled and retreated. Such range expansion and contraction can be explained by the social nature of sea otters, which acts to slow dispersal away from groups. Otter densities at Cojo Anchorage are now approaching equilibrium levels reported for central California. As in central California, otters rested in and near kelp forest habitat, but used deeper water for foraging. Together, these observations suggest habitat in the Santa Barbara Channel can still support sea otters, but range expansion of otters into southern California will be episodic due to social dynamics.